Extending the Marshallian industrial districts framework: framing types of multinationals - José Luis Hervás Oliver; Carles Boronat Moll; Maria Eizaguirre; Juan Antonio Marquez Garcia (Investigaciones Regionales - Journal of Regional Research)
In this study, we reflect on multinationals and their challenge to the established paradigm of Marshallian Industrial Districts (MIDs). Recently, scholars have begun to show a reorientation of the MID framework towards addressing topics that were not central to the mainstream MID framework, such as multinationals. We elaborate on and discuss the effects of multinationals in districts, a topic that demands further research and theoretical integration. We argue that future research should delve into questions around the development and empirical testing of multinationals in MIDs, proposing new lines of inquiry to strengthen the MID framework.